A non‐invasive NMR relaxometric characterization of the cyclododecane–solvent system inside porous substrates1. (16th September 2014) - Presciutti, F.; Doherty, B.; Anselmi, C.; Brunetti, B. G.; Sgamellotti, A.; Miliani, C.; Capitani, Donatella; Proietti, Noemi
<x xml:space="preserve">Abstract</x> With the aim of deepening the knowledge on the behavior of cyclododecane (CDD) as a temporary consolidant agent for weathered stones, NMR longitudinal and transverse relaxation decays have been exploited to follow the distribution of cyclododecane solutions into porous matrices. By measuring as function of time the relaxation decay constants of CDD solutions dropped onto porous supports, it has been possible to differentiate the step encompassing the solvent evaporation, which determines the consolidant migration within the matrix, from that governing the consolidant sublimation, which is related to the consolidation effectiveness over time. Copyright © 2014 John Wiley & Sons, Ltd.